Answer:
equal
Step-by-step explanation:
Answer:
14
Step-by-step explanation:
to find the answer to this you would have to ethier convert 1 3/4 to 1.75 or multiply top heavy fractions
converted way
1.75x8= 14 - stays the same
nonconverted way
7/4 x 8/1 = 56/4 = 14
etheir way you get the same answer
Answer: X=-7
Step-by-step explanation:
Using PEMDAS;
Step 1: Distribute the "3" in the part of the equation "3(x-2)"
3x - 6
Step 2: Consider the equation as a whole with the newly part of the equation from step 1, as it is a part of the equation
Therefore, re-written as,
3x - 6 + 48 = -3x
Step 3: Evaluate the re-written equation
Using basic mathematics skills, we can evaluate the following,
3x - 6 + 48 = -3x ➡ -6 + 48 = -6x ➡ 42 = -6x ➡ -7 = x
As shown, the answer is x=-7.
Answer:
B) −2
Explanation:
When x is positive then y is positive integer.
When x is negative then y is negative integer.
<u>For Option A</u>
- y = -1 [x is negative so is y]
<u>For Option B</u>
- y = 1 [<u>x is negative</u> but <u>y is positive</u>]
<u>For Option C</u>
- y = 7 [x is positive so is y]
<u>For Option D</u>
- y = 9 [x is positive so is y]